Elaboración y valoración del hierro en el pan enriquecido con harina de quinua (Chenopodium quinoa w.) y soja (Glycine max) - Mendoza Pérez, Diana Gloria (2019)
Objetive: To develop and evaluate the iron in enriched bread flour quinoa (Chenopodium quinoa W.) and soybeans(Glycine max), for this purpose, enriched bread, raising two formulations. Materials and Methods: We evaluatedthe amount of iron in the quinoa and soy flour, acceptability test and evaluation of the amount of iron in the finalproduct was also breads made proximal analysis, Total Quality in the Laboratory National Agrarian University laMolina (UNALM). Results: The results of iron in the final product for the first formulation were 6.2 mg / 100 g,second formulation 6.0 mg / 100 g, showed a significant difference in iron content with popular French bread. In thetest of acceptability presented greater acceptance for the first formulation. Conclusions: The bread enriched withquinoa and soy flour not only contains higher amounts of iron against the French bread, also in proteins containingessential amino acids, making this a highly nutritious bread.